Complex/Archetype/Symbol in the Psychology of C.G. Jung - Jacobi, Jolande (Bollingen Series (General) Ser., 2020)
As an associate of C. G. Jung for many years, Jolande Jacobi is in a unique position to provide an interpretation of his work. In this volume, Dr. Jacobi presents a study of three central, interrelated concepts in analytical psychology: the individual complex, the universal archetype, and the dynamic symbol.